Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1159/000493016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of PITX2 DNA Methylation to Predict Outcome in High-Risk Breast Cancer Patients Treated with Anthracycline-Based Chemotherapy

Abstract: Background: Breast cancer patients at high risk for recurrence are treated with anthracycline-based chemotherapy, but not all patients do equally benefit from such a regimen. To further improve therapy decision-making, biomarkers predicting outcome are of high unmet medical need. Methods: The percent DNA methylation ratio (PMR) of the promoter gene coding for the Paired-like homeodomain transcription factor 2 (PITX2) was determined by a validated methylation-specific real-time polymerase chain reaction (PCR) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 33 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…The clinical validation of the test was initially performed in the study that included 205 archival FFPE breast cancer samples of lymph node-positive (LN + ), estrogen receptor-positive (ER + ), HER2-negative patients (HER2 − ), treated with adjuvant anthracycline-based chemotherapy. This study reported that the test allowed to stratify patients undergoing adjuvant anthracyclinebased chemotherapy regarding disease-free survival, with HR 2.74 (95% CI 1.65-3.54; p < 0.001) [90].…”
Section: Breast Cancermentioning
confidence: 93%
“…The clinical validation of the test was initially performed in the study that included 205 archival FFPE breast cancer samples of lymph node-positive (LN + ), estrogen receptor-positive (ER + ), HER2-negative patients (HER2 − ), treated with adjuvant anthracycline-based chemotherapy. This study reported that the test allowed to stratify patients undergoing adjuvant anthracyclinebased chemotherapy regarding disease-free survival, with HR 2.74 (95% CI 1.65-3.54; p < 0.001) [90].…”
Section: Breast Cancermentioning
confidence: 93%
“…DNA methylation‐mediated gene inactivation was found in various cellular signalling pathways which influence transcription of tumour suppressor genes involved in DNA repair, hormonal signal transduction, cell adhesion, drug degradation and apoptosis 6,44 . Moreover, it has been shown, that epigenetic markers can be of clinical relevance in breast cancer 45‐50 …”
Section: Discussionmentioning
confidence: 99%
“…If the PMR obtained is equal to or lower than 12, the patient is likely to benefit from anthracycline-based chemotherapy. In contrast, if the PMR obtained is higher than 12, an alternative treatment may be proposed, because the patient has a lower probability of responding to anthracycline-based chemotherapy 20 .…”
Section: Therascreen Pitx2 Rgq Pcr Kit -Standard Pitx2 Workflowmentioning
confidence: 99%
“…DNA methylation patterns such as methylation status of the pituitary homeobox gene 2 (PITX2) play a key role in several cancer indications [6][7][8][9][10][11][12] including breast cancer [13][14][15][16][17] and published data of a Research Use Only (RUO) PITX2 DNA methylation assay using fresh-frozen tissue showed that PITX2 DNA methylation can be a predictive marker for response to adjuvant anthracycline-based chemotherapy in breast cancer 18 . The CE-marked therascreen ® PITX2 RGQ PCR Kit by QIAGEN was entering the market in 2018 as clinically validated biomarker test for breast cancer [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation